Revealing the secret life of skin ‐ with the microbiome you never walk alone - Sfriso, R.; Egert, M.; Gempeler, M.; Voegeli, R.; Campiche, R. (International journal of cosmetic science, 2020)
The human skin microbiome has recently become a focus for both the dermatological and cosmetic fields. Understanding the skin microbiota, that is the collection of vital microorganisms living on our skin, and how to maintain its delicate balance is an essential step to gain insight into the mechanisms responsible for healthy skin and its appearance. Imbalances in the skin microbiota composition (dysbiosis) are associated with several skin conditions, either pathological such as eczema, acne, allergies or dandruff or non‐pathological such as sensitive skin, irritated skin or dry skin. Therefore, the development of approaches which preserve or restore the natural, individual balance of the microbiota represents a novel target not only for dermatologists but also for skincare applications. This review gives an overview on the current knowledge on the skin microbiome, the currently available sampling and analysis techniques as well as a description of current approaches undertaken in the skincare segment to help restoring and balancing the structure and functionality of the skin microbiota. Résumé Le microbiome de la peau humaine est récemment devenu un centre d'intérêt pour les domaines dermatologique et cosmétique. Comprendre le microbiote cutané, à savoir la collection de microorganismes vitaux vivant sur notre peau, et comment maintenir son équilibre délicat est une étape essentielle pour mieux comprendre les mécanismes responsables d'une peau saine et son apparence. Les déséquilibres dans la composition microbiotique de la peau (dysbiose) sont associés à plusieurs affections cutanées, soit pathologiques comme l'eczéma, l'acné, les allergies ou les pellicules, soit non pathologiques comme la peau sensible, irritée ou sèche. Par conséquent, le développement d'approches qui préservent ou restaurent l'équilibre naturel et individuel du microbiote représente une nouvelle cible non seulement pour les dermatologues mais aussi pour les experts en cosmétiques. Cette revue donne un aperçu des connaissances actuelles sur le microbiome cutané, les techniques d'échantillonnage et d'analyse actuellement disponibles ainsi qu'une description des approches actuelles entreprises dans le segment des soins de la peau pour aider à restaurer et équilibrer la structure et la fonctionnalité du microbiote de la peau. The human skin microbiome has recently become a focus for both the dermatological and cosmetic fields. Understanding the skin microbiota and how to maintain its delicate balance is an essential step to gain insight into the mechanisms responsible for healthy skin and its appearance. This review gives an overview on the current knowledge on the skin microbiome, the currently available sampling and analysis techniques as well as a description of current approaches undertaken in the skin care segment to help restoring and balancing the structure and functionality of the skin microbiota.